Establishment of an American Branch-Campus Model of Higher Education: Qatar's Early Goals, Rationales, and Challenges - Pamela Walsh (Athens Institute for Education and Research, 2019)
This study presents original research findings of a qualitative study of Qatar's international higher-education branch-campus model, which in 2016 hosted 11 international branch campuses, among the most of any country then. Few studies have examined the rationales, goals, and challenges of the branch-campus model from a host country's perspective. This paper asks two central questions: 1) Why did Qatar partner with six North American universities to establish six international branch campuses between 2001and 2008 and 2) what were the challenges during the early years of operations from the Qatari and branch-campus leadership perspectives? This study's primary data-collection method was face-to-face, open-ended interviews. I interviewed 18 participants in Qatar and recruited based on potential participants' positions relative to the establishment, oversight, and governance of the six branch campuses. I also included executives and directors from the government of Qatar, Qatar Foundation, and leadership of the six branch campuses. I used extant documents, such as annual reports, strategic plans, government reports, speeches, and popular-media articles as additional data sources. Findings included rationales and goals related to pedagogy, sociocultural development, societal engagement, development of research capacity, and Qatar's status as a leader and driver of change in the Arab Gulf region and beyond. Challenges included sociocultural issues, tensions between the international branch-campus leaderships and their home institutions, and conflicting expectations between the branch campuses and Qatar Foundation. These findings include in-depth and new insights into host-country goals and aspirations, and challenges experienced by U.S. and host-country partners, and how these challenges have been addressed.